Introduction to the Law Library CD-based multimedia package / Chan Yuet Lai - Chan , Yuet Lai (2000)
This project, Introduction to the Law Library, is a CD-based multimedia package which main objective is to provide information about the library to the new law students during orientation week. This proposal provides an overview about the development of this package. Literature reviews provide ideas and enable developers to have a clearer picture in developing a system. For this project, review has been done on multimedia development, development strategy, authoring tools, similar packages, and others library web pages. From the findings, lots of information for developing this project was obtained and the results were all shown in the chapter two of this proposal. The System Development Life Cycle is chosen as the development strategy for this project by using the Macromedia Director 7 authoring tool. Once this project is developed, it consists of features such as background and history, location, floor plan and operation hours, library collection, library facilities, services, memberships, and rules and regulations, information on CDROM database and introduction to OPAC System, as well as borrowing, returning and booking procedures, and the fine system according to different kinds of memberships.